Depth frame loss concealment for wireless transmission utilising motion detection information - Ranjbari, Mohamadreza (2014)
Three dimensional (3D) television systems have received increasing attention, with the remarkable developments of video techniques. Transferring video over wireless channels, which is generally an error prone channel, is very susceptible to the transmission errors. 3D video is more vulnerable to transmission errors than conventional two dimensional (2D) video due to its left and right views. On top of that, existing error concealment algorithms for the 2D videos are not suitable to apply to the 3D video and they may even degrade the quality of the synthesized view in the 3D video. In regard to quality of the 3D video, the main challenge is to provide a high quality synthesized view for the viewers. It can be achieved considering the structure of the 3D video using proper methods which are designed for the 3D video. In the 3D video transmission, whenever frame loss happens, there is a higher probability of depth frame loss than the colour frame due to less priority of depth frame in the transmission. Proper depth frame concealment should be applied in order to improve perceived quality of the video. Considering high packet loss rate in error prone channels like wireless channels, it is crucial to apply error concealment to compensate the frame losses in the transmission. While a number of algorithms has been proposed to address this issue, most of the existing approaches tend to increase the transmission in terms of sending redundant information regarding error concealment. In this thesis, the aforementioned issues are addressed. By focusing mainly on concealment of depth frame loss at the decoder, the quality of transmitted 3D video is improved in the synthesised views. Two concealment methods, namely Decision Making based on Pixel Value (DM-PV) and Depth Frame Concealment based on Motion Detection (DFC-MD) are proposed to conceal the depth frame loss in the 3D video transmission. The methods are able to facilitate a frame copy algorithm and a high correlation of colour and depth frames to conceal depth frame loss. The first proposed method, inspired by DM-PV, makes its decision whether to copy the last frame or replacing a blank frame by pixel value of the corresponding frames in the colour sequence. The second method also facilitates the frame copy algorithm in the depth sequence, however, the high motion blocks inside the frame that intended to be copied are found and then they will be interpolated; furthermore, the low motion blocks remain unchanged in the frame. The proposed error concealment method which is based on decision making by pixel value technique can prevent distortion on left and right views. The proposed method is able to improve the quality of video in comparison with frame copy algorithm. The feasibility and performance of the proposed method based on motion detection error concealment is evaluated analytically by considering different packet and frame loss rates. The results are compared with existing 3D video frame concealment methods in terms of PSNR for low depth intensity sequences and the average improvement is about 13%. Moreover, the proposed method can improve quality of video in terms of SSIM in comparison with the existing frame copy method for the 3D sequences with moderate depth intensity.